2019
DOI: 10.1002/mpr.1813
|View full text |Cite
|
Sign up to set email alerts
|

Psychotic disorders hospitalizations associated with cannabis abuse or dependence: A nationwide big data analysis

Abstract: Objectives We aimed to describe and correlate the hospital panorama of psychotic disorders (PD) with cannabis use (CU) trends in all Portuguese public hospitals. Methods We conducted a retrospective observational study that analysed all hospitalizations that occurred in Portuguese public hospitals from 2000 to 2015. Hospitalizations with a primary diagnosis of PD or schizophrenia were selected based on Clinical Classification Software diagnostic single‐level 659. Episodes associated with CU were identified by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…Further independent evidence comes from Portugal that has registered a steady increase in the rate of hospital admissions for psychotic disorders with comorbid CUD. 45 Similar data were reported in Denmark. 59 Both countries have seen a rise in the potency of available cannabis over the same period.…”
Section: Cannabis and Psychosissupporting
confidence: 74%
“…Further independent evidence comes from Portugal that has registered a steady increase in the rate of hospital admissions for psychotic disorders with comorbid CUD. 45 Similar data were reported in Denmark. 59 Both countries have seen a rise in the potency of available cannabis over the same period.…”
Section: Cannabis and Psychosissupporting
confidence: 74%
“…32 A limited number of studies have further identified increased rates of psychotic disorders associated with state and regional cannabis legalization in the US and with national policies in Canada and Portugal. [33][34][35][36] As states continue to introduce cannabis legislation, a thorough and comprehensive understanding of their potential health outcomes is essential. Yet to our knowledge, no studies have examined trends in psychosis-related outcomes as a function of medical and recreational cannabis laws across all US states.…”
Section: Introductionmentioning
confidence: 99%
“…As for people with mood disorders, the severity is generally higher than that associated with other comorbidities, mainly in terms of family problems and psychological distress, while recognizing the negative impact of the association between drug use and mood disorders, such as, problems in keeping up a professional activity and financial stability (Frank et al 2019;Winkelman et al 2018). Another condition associated with greater severity is psychotic disorders, as in other studies (Gonçalves-Pinho et al 2019;Hanna et al 2017), although we are at a time in which discussions are taking place about the benefit of using some substances in the treatment of mental disorders (Black et al 2019;Khan et al 2020). It is clear that the association of more comorbidities is progressively related to greater severity, as in other studies (Winkelman et al 2018), especially with regard to mood disorders, which are more prevalent in female users (Keyser-Marcus et al 2015).…”
Section: Discussionmentioning
confidence: 89%